1970
DOI: 10.3329/bjo.v17i1.7616
|View full text |Cite
|
Sign up to set email alerts
|

Cut throat injury: review of 67 cases

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 3 publications
6
37
0
Order By: Relevance
“…[5] There is reported incidence of 10.45% suicidal CTI. [6] In our study, the incidence of suicidal CTI is alarmingly high with as high as 31.48% of all CTI. Appropriate measures can save lives in the vast majority of patients with CTI.…”
Section: Discussionmentioning
confidence: 92%
“…[5] There is reported incidence of 10.45% suicidal CTI. [6] In our study, the incidence of suicidal CTI is alarmingly high with as high as 31.48% of all CTI. Appropriate measures can save lives in the vast majority of patients with CTI.…”
Section: Discussionmentioning
confidence: 92%
“…(10) Onatoi et al found male preponderance in CTIs in their study and concluded that it may be due to their risk taking behavior, active participation and frequent involvement in interpersonal violence. (11) In a study by Aich et al majority of the patient's belonged to young age between 21 to 30 years. In contrast our study shows the commonest age group involved is 19(39.58%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, on patients who had cut throatinjuries done in Tanzania, interpersonal conflict (24.4%) was the most common factor found for homicidal injuries while psychiatric illness(16.2%) and road traffic accidents (9.2%) were the most frequent ones for the suicidal attempts and accidental injuries, respectively 10 . In a similar study by Ozdemir, the most dominant reason turned out to be mental illness with a prevalence of 26.7%,injuries due to honor reasons were second in order with 20%, the other reasons being domestic violence (13%), economical reasons (13%), and gang fights (7%).…”
Section: Discussionmentioning
confidence: 99%